1997
DOI: 10.2337/diacare.20.9.1388
|View full text |Cite
|
Sign up to set email alerts
|

NIDDM and Blood Pressure as Risk Factors for Poor Cognitive Performance: The Framingham Study

Abstract: History and duration of NIDDM and high blood pressure are significant risk factors for poor cognitive performance. Hypertensive people with NIDDM are at greatest risk for poor performance on tests measuring visual organization and memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
219
3
8

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(250 citation statements)
references
References 0 publications
20
219
3
8
Order By: Relevance
“…In our study we couldn't evaluate attention and executive function as there was no provision in our study tool to evaluate those functions. Elias et al (1997) also reported increased risk of a low score (bottom 25%) for those with diabetes on five of eight tests (immediate and delayed logical memory, digit span forward, word fluency, and similarities) which is consistent with our study. Arvanitakis et al (2006) showed diabetes was not associated with abnormal episodic memory, working memory, or visuospatial ability.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our study we couldn't evaluate attention and executive function as there was no provision in our study tool to evaluate those functions. Elias et al (1997) also reported increased risk of a low score (bottom 25%) for those with diabetes on five of eight tests (immediate and delayed logical memory, digit span forward, word fluency, and similarities) which is consistent with our study. Arvanitakis et al (2006) showed diabetes was not associated with abnormal episodic memory, working memory, or visuospatial ability.…”
Section: Discussionsupporting
confidence: 82%
“…Ruis et al (2009) had shown that diabetes duration was associated with the effect size (cognitive decline) of the study: the longer the known diabetes duration, the bigger the effect size which was substantiated by other studies. In the Study of Osteoporotic Fractures (Gregg et al, 2000), there was a trend of increasing risk of cognitive decline with increasing duration of diabetes, and in the Framingham study (Elias et al, 1997), each 5-year increment between diabetes diagnosis and cognitive assessment was associated with lower scores on tests of logical memory, word fluency, and similarities. However, studies have also shown cognitive outcome variable to be independent of duration of diabetes which have stirred up controversy regarding this issue (Manschot et al, 200831).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus has been associated with decrements in cognitive performance and dementia in cross-sectional and longitudinal studies [1][2][3][4]. A recent review indicates that individuals with diabetes have a greater risk of cognitive decline and a greater risk of developing dementia than do non-diabetic individuals [3].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that elevated blood pressure not only predicts later-life changes on measures of brain morphology [45,46] and cognitive function [45,47]-particularly on speeded tests like the DSST [37,48], but could act synergistically with diabetes [49] or insulin resistance [50] to increase the severity of neurocognitive impairment. Higher blood pressure might adversely affect mental efficiency via vascular and/or neural pathways.…”
Section: Discussionmentioning
confidence: 99%